ANALYSIS OF PUBLIC BEHAVIOR IN THE FACE OF THE CORONA VIRUS PANDEMIC (COVID-19) IN THE VILLAGE OF PALUR DISTRICT OF MOJOLABAN SUKOHARJO DISTRICT - Annisa, Rohani Sofik Nur; Rohsulina, Pranichayudha; Wijayanti, Ary (Journal of Geography Science and Education, 2020)
The study aims to learn: (1) the behavior of palur village people in the face of the pandemic. (2) government policy understanding of social distension. (3) the impact of a pandemic in palur village of mojolaban district sukoharjo district district district.The methods used in this study are qualitative disticized, depicting or enhancing and learning about people's behavior in dealing with the corona virus pandemic (covid-19) in palur village, government policies on social distension and knowing the effects of the corona virus (covid-19) in palur village. The data-gathering technique used is through direct field observations, interviews and documenting. The data analysis techniques used are descriptive data analysis and chart data.The results of the study are: (1) citizens are more accustomed to clean and healthy living, implementing health protocols in accordance with government requirements. (2) palur villagers are aware of the social censorship and prevention efforts in dealing with pandemics in accordance with government appeals, but there are still a few places where crowds are. (3) the impact of inequality on people is social, economic and health.